2018
DOI: 10.1590/s1519-99402018000300001
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and partition of macronutrients in Pennisetum purpureum cv. Roxo managed under different growth ages and seasons

Abstract: SUMMARY The objective of this study was to evaluate the macronutrient accumulations in leaf, stem, and shoot of elephant grass cv. Roxo. The treatments consisted of seven growth ages (9, 18, 27, 36, 45, 54, and 63 days) and three growing seasons (rainy, transition, and dry). A completely randomized design and a split-plot time arrangement were used, where the ages were the plots and the seasons the subplots, with three replications. Interaction between the factors age and season of cultivation for the contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…When extrapolating these results for a full year, the authors found similar values of N extraction to those obtained in this experiment for plants submitted to TWN, TWA and TFN treatments, P extraction in the TFA treatment, and higher K values in all treatments. This is explained by the potassium fertilization dose that was used in the cited study 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When extrapolating these results for a full year, the authors found similar values of N extraction to those obtained in this experiment for plants submitted to TWN, TWA and TFN treatments, P extraction in the TFA treatment, and higher K values in all treatments. This is explained by the potassium fertilization dose that was used in the cited study 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The macronutrient extraction capacity of elephant grass (an important forage species in Brazilian livestock) depends mainly on soil fertilization and crop management 15 , 16 . The influence of different fertilizer doses, types of fertilizers applied, cutting ages, season, cultivars and other variables that affect productivity of this grass has been addressed in several studies 17 – 19 , however the response of this plant to application of sanitary sewage has not been mentioned.…”
Section: Introductionmentioning
confidence: 99%